Glucose-regulated protein 78 is essential for cardiac myocyte survival. Issue 12 (December 2018) - Wang, Xiaoding; Bi, Xukun; Zhang, Guangyu; Deng, Yingfeng; Luo, Xiang; Xu, Lin; Scherer, Philipp; Ferdous, Anwarul; Fu, Guosheng; Gillette, Thomas; Lee, Amy; Jiang, Xuejun; et al.
Abstract Secretory and transmembrane proteins rely on proper function of the secretory pathway for folding, posttranslational modification, assembly, and secretion. Accumulation of misfolded proteins in the endoplasmic reticulum (ER) stimulates the unfolded protein response (UPR), which communicates between the ER and other organelles to enhance ER-folding capacity and restore cellular homeostasis. Glucose-regulated protein of 78 kDa (GRP78), an ER-resident protein chaperone, is a master regulator of all UPR signaling branches. Accumulating studies have established a fundamental role of GRP78 in protein folding, ER stress response, and cell survival. However, role of GRP78 in the heart remains incompletely characterized. Here we showed that embryos lacking GRP78 specifically in cardiac myocytes manifest cardiovascular malformations and die in utero at late gestation. We went further to show that inducible knockout of GRP78 in adult cardiac myocytes causes early mortality due to cardiac cell death and severe decline in heart performance. At the cellular level, we found that loss of GRP78 increases apoptotic cell death, which is accompanied by reduction in AKT signaling and augmentation of production for reactive oxygen species. Importantly, enhancing AKT phosphorylation and activity leads to decreases in oxidative stress and increases in cardiac myocyte survival. Collectively, our results demonstrate an essential role of GRP78 in ensuring normal cardiogenesis and maintaining cardiac contractility and function.